Tradable mobility permits in a monocentric city with pre-existing labor taxation: A general equilibrium perspective - Diego Candia; Erik T. Verhoef (Tinbergen Institute, 2021)
This paper considers tradable mobility permit schemes in a monocentric city with a distorting labor tax. Three schemes are analyzed, that differ by the (spatial) allocation of permits to households. Numerical results show that the scheme with permits allocated in proportion to labor supply reaches about 99.9% of the first-best welfare, being the only welfare-increasing scheme for higher levels of labor tax, and being more efficient than the second-best tax for levels of the labor tax of 20% or higher. This is due to the welfare gains of incentivizing labor supply, which has an effect similar to the revenue recycling effect of conventional road pricing, but that can be better optimized by the social planner by exploiting spatial differentiation. When permits are allocated on the basis of households' residential distance from the CBD, a spatially differentiated component leads to higher welfare levels than with the third scheme considered, which is the allocation in proportion to households' kilometers traveled.
Keywords: R41; R48; H23; 330; Tradable permits; Congestion pricing; Monocentric city; Revenue recycling; Spatial general equilibrium